2001
DOI: 10.1017/s0021963001007119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Measures of ADHD Symptomatology: A Multivariate Genetic Analysis

Abstract: The phenotypic and genetic interrelationships underlying ADHD symptomatology assessed by various instruments were examined on a sample of 735 male and 819 female same-sex twin pairs, aged 8 to 16 years, participating in the first phase of the Virginia Twin Study of Adolescent Behavioral Development (VTSABD). Multivariate analyses were applied to parental and teacher ratings from an investigator-based interview, the CAPA, and three questionnaires (the CBCL and the Rutter Parent and Teacher Scales). Results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 0 publications
9
36
0
Order By: Relevance
“…When results of the Rutter-A and -B scales or from the parent or teacher rated DBRS were compared (Table 1), teacher ratings often resulted in lower heritability estimates (around 50%) than parent ratings and additionally described shared and non-shared environmental effects [41,67,97,99,106]. Besides possible measurement error, findings imply that parents and teachers might rate different ADHD behavior, which has explicitly been shown for differences in the ratings of mothers and fathers [43,113].…”
Section: Rater Effectsmentioning
confidence: 94%
See 2 more Smart Citations
“…When results of the Rutter-A and -B scales or from the parent or teacher rated DBRS were compared (Table 1), teacher ratings often resulted in lower heritability estimates (around 50%) than parent ratings and additionally described shared and non-shared environmental effects [41,67,97,99,106]. Besides possible measurement error, findings imply that parents and teachers might rate different ADHD behavior, which has explicitly been shown for differences in the ratings of mothers and fathers [43,113].…”
Section: Rater Effectsmentioning
confidence: 94%
“…Several studies additionally assessed the bivariate heritability of attention problems and hyperactive-impulsive symptoms to elicit, if attention problems and hyperactive-impulsive problems were mediated by the same or different genetic risk factors. Despite an early finding of high bivariate heritability suggesting that the same genetic influences contribute to attention problems and hyperactivity/impulsivity in DSM-III [96], more recent studies resulted in the findings of common as well specific genetic effects for each subtype [52,65,67,120]. These findings are supported by a metaanalysis of family studies which also reported small subtype-specific transmission effects [102].…”
Section: Subtype Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears from twin studies that this is partially true, with studies consistently showing genetic influences common to both reports (e.g. Thapar et al 11 , Nadder et al 34 and Martin et al 32 ). However, the same studies show informant-specific effects suggesting that some genes contribute to phenotypes differentially indexed by informant sources, an observation that should be borne in mind when comparing molecular genetic data derived from different study designs using different reporters.…”
Section: Combined Parent and Teacher Reportsmentioning
confidence: 98%
“…54 In the present study, our quantitative TDT findings for the calcyon gene show a higher degree of similarity between the analyses of parent and teacher ratings of inattentive behaviours than between the corresponding analyses of hyperactive/impulsive behaviours. The significance of this is unclear, although we note that only moderate genetic correlations between raters has been suggested by twin studies, 55,56 and it is thought that this may be due to different sets of genes underlying what is observed and reported by the two informants. 57 Thus, the use of different raters, by providing supplementary information, should be valuable in elucidating the complex genotype/phenotype relationships in ADHD.…”
Section: Discussionmentioning
confidence: 56%